Pengaruh Job Insecurity, Terhadap Keinginan Berpindah Kerja Dengan Kepuasan Kerja Dan Komitmen Organisasional Sebagai Variabel Intervening - Gabriela Meta Paramastri Kuding; Ratnawati Kurnia (Universitas Multimedia Nusantara, 2011)
This study aims to obtain empirical evidence about the effect of job insecurity toward job turnover intentions with job satisfaction and organizational commitment as intervening variable The samples in this study are employees who worked at the television industry in Jakarta. Sampling method used was convenience sampling. Tests used in this study are validity testing, reliability testing, the classic assumption testing, simple regression and path analysis testing. Results of the first hypothesis toward showed that there was significant influence of job insecurity towards job turnover intentions. Result of this study showed that organizational commitment and job satisfaction were not intervening variable in the relations between job insecurity and job turnover intention. Keyword: job insecurity, organizational commitment, job satisfaction, turnover intentions of the employees